Political connections, informational asymmetry, and the efficient resolution of financial distress - ANEY, Madhav S. (Institutional Knowledge at Singapore Management University, 2022)
We show that securities issued by a distressed firm, often through exchange offers, providethe most efficient resolution of financial restructuring. Information asymmetry between thefirm-bank coalition and small bondholders gives rise to other forms of distress resolutionsuch as refinancing, public workout, and the inefficiency of liquidation. We find that politicallobbying by the firm-bank amplifies these inefficiencies and inhibits the development of privatemarket for distressed securities. Cross-country evidence is consistent with this and indicatesthat improved creditor rights, and information facilitating credit bureaus interact in reducingthe likelihood of inefficient distress resolution.